Fulde–Ferrell state in superconducting core/shell nanowires: role of the orbital effect. (2nd November 2017) - Mika, Marek; Wójcik, Paweł
Abstract: The orbital effect on the Fulde–Ferrell (FF) phase is investigated in superconducting core/shell nanowires subjected to the axial magnetic field. Confinement in the radial direction results in quantization of the electron motion with energies determined by the radial j and orbital m quantum numbers. In the external magnetic field, the twofold degeneracy with respect to the orbital magnetic quantum number m is lifted which leads to the Fermi wave vector mismatch between the paired electrons, ( k, j, m, ↑ ) ↔ ( − k, j, − m, ↓ ) . This mismatch is transferred to the nonzero total momentum of the Cooper pairs, which results in a formation of the FF phase occurring sequentially with increasing magnetic field. By changing the nanowire radius R and the superconducting shell thickness d, we discuss the role of the orbital effect in the FF phase formation in both the nanowire-like ( R / d ≪ 1 ) and nanofilm-like ( R / d ≫ 1 ) regime. We have found that the irregular pattern of the FF phase which appears for the case of the nanowire-like regime, for the nanofilm-like geometry evolves towards the regular distribution in which the FF phase stability regions emerge periodically between the BCS states. The transition between these two different phase diagrams is explained as resulting from the orbital effect and the multigap character of superconductivity in the core/shell nanowires.